If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 16x = 17x + 2 Reorder the terms: 6 + 16x = 2 + 17x Solving 6 + 16x = 2 + 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 6 + 16x + -17x = 2 + 17x + -17x Combine like terms: 16x + -17x = -1x 6 + -1x = 2 + 17x + -17x Combine like terms: 17x + -17x = 0 6 + -1x = 2 + 0 6 + -1x = 2 Add '-6' to each side of the equation. 6 + -6 + -1x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 2 + -6 -1x = 2 + -6 Combine like terms: 2 + -6 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x | | 0.5x+0.3=1.2 | | 5(12-x)=25 | | 2x(8x-5)=(5-4x)2 | | 15y^3-123y^2+24y= | | 2x+5+2x=1 | | 7y=-19y+2 | | 15+5(3c-2)= | | -6(8x-3)=-36+6x | | 5(a+4)+3(6a-7)= | | 4x-3=-2x+27 | | 12x+162=15x | | 25+30v+26+21v=37v+11v | | 3x+9=6x-3(x+3) | | 3(x+2)=5(x-3)-13 | | 12-7n=6(n-4)-4n | | 8-2n+2n=8 | | 111-5v=71 | | 24.3=2I+2a | | 6x+8+16=10x | | 2x+4+5x-8=90 | | -2(3x-1)=-4-3x | | 6x+8=16+10x |